Transluminal Nd:YAG laser embolysis – A reasonable method to reperfuse occluded branch retinal arteries - Stanca, Horia T.; Petrović, Žarko; Munteanu, Mihnea (Vojnosanitetski pregled, 2014)
Introduction. Central retinal artery occlusion (CRAO) and branch retinal artery occlusion (BRAO) result in partial or complete retinal ischemia and sudden loss of vision; at this moment, there is no effective therapy for CRAO and BRAO. Transluminal Nd:YAG laser embolysis (TYE) represents a therapeutic approach used for retinal vascular occlusive diseases. The main indication is branch retinal artery occlusion with visible embolus; for central retinal artery occlusion this tehnique is hardly applicable. The principle of this method consists of intravascular embolus breakage using the 1064 nm Nd:YAG laser, focused on the embolus surface. Case report. We presented 5 cases with BRAO, 3 with infero-temporal and 2 with supero-temporal BRAO, all of them treated with TYE, with variable results. All the patients had a visible embolus within the BRA, the laser applications being delivered directly to the embolus. Conclusion. Despite our short-term experience regarding this therapeutical approach, we can resume that the moment of emboli distruction, as close as possible to the onset of the occlusion, is decisive for regaining vision and that applying the procedure correctly is superior to observation in most cases. Worldwide experience with TYE is still limited, but the technique seems feasible also when treating CRAO caused by visible emboli on the optic disc surface. This most certainly calls for random trials for identifying precisely the role of TYE in treatment of retinal occlusion pathology, though the relatively small number of properly diagnosed cases affects this objective. In all cases, the risks of TYE must be weighed against the possibility of severe and permanent loss of vision secondary to retinal artery occlusions.